(untitled) (Eurasian Journal of Humanities and Social Sciences, 2024)
The legal basis of the development of ideological-ideological competence in students is highlighted in the article, the author revealed the essence of the concepts of "socially active legal behavior", "legal consciousness" and "legal culture" based on the analysis of theoretical materials. Ideological prevention is a set of educational, ideological works of various forms carried out by social institutions, and this important process includes today’s system of ideological education.